Holling-Tanner Predator-Prey Model with Type-IV Functional Response and Harvesting - Gazi, Nurul Huda; Biswas, Subrata Kumar (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper we modify Holling-Tanner predator-prey model by using type-IV functional response in prey species in lieu of type-II functional response. Harvesting is used in predator as well as prey species. This model is compared with a special type of Kolmogorov model. In the case of quadratic harvesting, the fixed points are computed after nondimensionalization. For the non-existence of periodic orbits in the first quadrant we apply a condition of the general Kolmogorov model to exist a Dulac function. We show that this system does not have periodic orbits with the help of numerical simulation and graphical representation.